2008
DOI: 10.5367/000000008783554893
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Inbound Tourism to South Africa

Abstract: South Africa has experienced a significant increase in tourist arrivals over the past ten years. The challenge is to sustain this growth and therefore it is important to understand the factors that influence inbound tourism to South Africa. The purpose of this article is to identify the various determinants of inbound tourism to South Africa from different source markets (categorized in continents). Time series quarterly data from 1993 to 2004 is used in the analysis of tourist arrivals. Cointegration analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
60
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 22 publications
14
60
0
2
Order By: Relevance
“…These results were also indicated by Du Plessis (2002), Heath (2002), Saayman and Saayman (2008) and Blanke and Chiesa (2013) (Travel and Tourism Competitiveness Report). In Porter's (1990) diamond of competitive advantage, safety and security is part of the demand conditions which constitute the standards of demand.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…These results were also indicated by Du Plessis (2002), Heath (2002), Saayman and Saayman (2008) and Blanke and Chiesa (2013) (Travel and Tourism Competitiveness Report). In Porter's (1990) diamond of competitive advantage, safety and security is part of the demand conditions which constitute the standards of demand.…”
Section: Resultssupporting
confidence: 71%
“…The moderate climate has always been one of the country's best assets, which confirm findings by Saayman and Saayman (2008) and the Travel and Tourism Competitiveness Report (Blanke & Chiesa 2013) concerning climate, natural resources and cultural resources as South Africa's best attractions.…”
Section: Results Of the Strengths And Weaknesses Of South Africasupporting
confidence: 67%
“…Some studies have briefly indicated that weather and climate are important factors motivating inbound travel to South Africa (Kim et al, 2000;Saayman, Saayman, 2008). In a review of literature on the effects of climate change on tourism in Africa, found that changes in weather events, such as precipitation, have the potential to negatively impact tourism in the region in a number of ways.…”
Section: Weather and Tourism In Southern Africamentioning
confidence: 99%
“…tourists (Saayman, Saayman, 2008). Third, as a developing country, South Africa has a much lower adaptive capacity than more developed countries, and consequently is less able to mitigate against and repair damages sustained during extreme weather events .…”
mentioning
confidence: 99%
“…researchers have suggested that there are a wide range of factors affecting tourism demand (Crouch, 1994;Lim, 1999;Saayman & Saayman, 2008). Very few of these demand models have included migration-related items as independent variables in the equations.…”
Section: Migration-induced Tourism Flowsmentioning
confidence: 99%